Alternative energy - Vandana, S. (New Delhi : APH, 2002)
"Alternative Energy systematically explores the most viable alternative sources of energy, discussing the technical, political, economic, and social feasibility of each technology in understandable terms. In addition, the book discusses the history of energy policy as well as current policy. Intended for courses in energy and public policy and for those interested in developing energy-efficient plans for sustainable communities, Alternative Energy will help readers become active participants in making future energy choices for their communities. Alternative Energy includes an interactive model of alternative energy mixes and estimated prices."--BOOK JACKET.
Why alternative energy and fuels? -- Studying public policy and alternative energy/fuels -- Overview of alternative energy and fuels and their uses -- Alternative energy/fuels as a public policy innovation -- Solar energy -- Wind energy -- Geothermal energy -- New century fuels and their uses -- Historical precedents: alternative energy/fuels and legitimacy issues -- Public policy, institutional developments, and policy interests -- Practical demonstration of the economics of alternative energy -- Conclusion: the future of alternative energy.
Includes bibliographical references and index.
Keywords: Energy policy -- United States; Renewable energy sources -- United States; Power resources -- Government policy -- United States